(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Objective. To present a clinical-psychometric model for assessing the stability of remissions in endogenous mental disorders, based on the integration of psychopathological, functional, and typological indicators. Materials and Methods. The study included 197 patients with endogenous mental disorders (ICD-10: F20–F33) who had been in remission for at least 6 months. PANSS and SOFAS scales were used to assess the condition, along with M. L. Agranovsky’s typology of remissions. A multifactorial risk analysis was performed using logistic regression, ROC analysis, and the calculation of odds ratios (OR, 95% CI). Results. Independent predictors of remission stability were: • pronounced clinical response (ΔPANSS ≥ 15; OR = 0.42; p = 0.002), • high level of social functioning (SOFAS ≥ 45; OR = 0.35; p = 0.001), • favorable remission types (IiRsLIL, ATR, NTR, TTR; OR = 0.28; p < 0.001), • high treatment adherence (OR = 0.31; p < 0.001). The prognostic model demonstrated high accuracy (AUC = 0.83; 95% CI: 0.78–0.88), sensitivity — 91.8%, specificity — 94.7%, and the Hosmer–Lemeshow test confirmed adequate calibration (p > 0.05). Conclusion. The developed clinical-psychometric model has high predictive value and can be applied in clinical practice to stratify patients by relapse risk and individualize preventive strategies.